Pengaruh Musik Instrumental terhadap Kecemasan Pasien pada Tindakan Perawatan Gigi dan Mulut - Yunizar, Vania R.; Mita Juliawati; Andayani, Lia H. (e-GiGi, 2024)
Abstract: Dental anxiety is feeling of fear when visiting a dentist for a dental procedures. Dental anxiety can be caused by many factors such as previous traumatic experience at the dentist, lack of understanding of the dental and oral care procedures, and unpleasant experiences of those around him/her about dental and oral care. Indicators of anxiety can be evaluate with the modified dental anxiety scale (MDAS) and the patient's systemic reaction, namely blood pressure. Reducing anxiety and blood pressure can be overcome with pharmacological and non-pharmacological techniques, one of which is instrumental music. This study aimed to determine the effect of instrumental music on patient anxiety in dental and oral care procedures. This was an experimental study conducted on 63 adult patients. Subjects filled out the MDAS questionnaire to evaluate their level of anxiety and were checked their blood pressure before and after treatment. Data were analyzed using the Wilcoxon test and one-way ANOVA to determine the effect of instrumental music on anxiety. The results showed significant differences in patient anxiety before and after being given instrumental music based on the MDAS questionnaire (p=0.000), systolic blood pressure (p=0.000), and diastolic blood pressure (p=0.000). In conclusion, instrumental music can reduce the patient's anxiety level. Keywords: dental anxiety; blood pressure; instrumental music; modified dental anxiety scale   Abstrak: Kecemasan dental merupakan rasa takut ketika akan melakukan kunjungan ke dokter gigi untuk suatu tindakan kedokteran gigi. Kecemasan dental dapat disebabkan oleh berbagai faktor seperti pengalaman yang traumatik sebelumnya saat ke dokter gigi, kurangnya pemahaman tentang prosedur perawatan gigi dan mulut yang akan dilakukan, serta pengalaman orang di sekitarnya tentang perawatan gigi dan mulut yang tidak menyenangkan. Indikator kecemasan dapat dinilai dengan modified dental anxiety scale (MDAS) dan reaksi sistemik pasien yaitu tekanan darah. Untuk menurunkan kecemasan dan tekanan darah dapat diatasi dengan teknik farmakologi dan non-farmakologi, salah satunya dengan menggunakan musik instrumental. Penelitian ini bertujuan untuk mengetahui pengaruh musik instrumental terhadap kecemasan pasien pada tindakan perawatan gigi dan mulut. Jenis penelitian ialah eksperimental yang dilakukan pada 63 pasien dewasa dengan mengisi kuesioner MDAS untuk melihat tingkat kecemasan dan dilakukan pengecekan tekanan darah sebelum dan setelah perawatan. Data dianalisis menggunakan uji Wilcoxon dan one way ANOVA untuk mengetahui pengaruh musik instrumental terhadap kecemasan.  Hasil penelitian mendapatkan perbedaan bermakna pada kecemasan pasien sebelum dan setelah diberi musik instrumental berdasarkan kuesioner MDAS (p=0,000), tekanan darah sistolik (p=0,000), dan tekanan darah diastolik (p=0,000). Simpulan penelitian ini aialah musik instrumental dapat menurunkan tingkat kecemasan. Kata kunci: kecemasan dental; tekanan darah; musik instrumental; modified dental anxiety scale